Advanced vat photopolymerization 3D printing of silicone rubber with high precision and superior stability - Zhongying Ji; Bingang Xu; Zhiyong Su; Xiaochen Wang; Yang Lyu; Sen Liu; Tao Wu; Xiaolong Wang (International Journal of Extreme Manufacturing)
Silicone rubber (SR) is a versatile material widely used across various advanced functional applications, such as soft actuators and robots, flexible electronics, and medical devices. However, most SR molding methods rely on traditional thermal processing or direct ink writing three-dimensional (3D) printing. These methods are not conducive to manufacturing complex structures and present challenges such as time inefficiency, poor accuracy, and the necessity of multiple steps, significantly limiting SR applications. In this study, we developed an SR-based ink suitable for vat photopolymerization 3D printing using a multi-thiol monomer. This ink enables the one-step fabrication of complex architectures with high printing resolution at the micrometer scale, providing excellent mechanical strength and superior chemical stability. Specifically, the optimized 3D printing SR-20 exhibits a tensile stress of 1.96 MPa, an elongation at break of 487.9%, and an elastic modulus of 225.4 kPa. Additionally, the 3D-printed SR samples can withstand various solvents (acetone, toluene, and tetrahydrofuran) and endure temperatures ranging from −50 °C to 180 °C, demonstrating superior stability. As a demonstration of the application, we successfully fabricated a series of SR-based soft pneumatic actuators and grippers in a single step with this technology, allowing for free assembly for the first time. This ultraviolet-curable SR, with high printing resolution and exceptional stability performance, has significant potential to enhance the capabilities of 3D printing for applications in soft actuators, robotics, flexible electronics, and medical devices.